Neonatal Mortality and Associated Factors Among Neonates Admitted to the Neonatal Intensive Care Unit of Dil Chora Referral Hospital, Dire Dawa City, Ethiopia, 2021: A Facility-Based Study - Thomas, Gelila; Demena, Melake; Hawulte, Behailu; Eyeberu, Addis; Heluf, Helina; Tamiru, Dawit (Frontiers in Pediatrics, 2022)
Background: Despite the incredible progress made in decreasing under-five mortality, neonatal mortality remains the main and slowly advancing contributor. Though all efforts were made to decline the death of a newborn, current information showed that newborn death is un averted and not a fastened agenda. This study aimed to assess neonatal mortality and its determinant among neonates admitted at Dil Chora Hospital in Dire Dawa city. Methods: Facility-based cross-sectional study design was employed. A total of 376 newborns were selected systematically from neonates admitted to the NICU of Dil Chora referral Hospital from June 1, 2017- December 31, 2020. Data were collected from medical records using a standard extraction checklist. The data were entered into Epi-data version 3.1 and then exported into SPSS version 24 for statical analysis. Bivariate and multivariate analyses were employed to identify the association between independent variables and neonatal death. Result: The prevalence of neonatal death was 11.4% (95% CI:9.44 - 13.36). The majority 37 (86.05%). of neonates were died within seven days of life. The most common causes of admission include perinatal asphyxia (55.3%), Hypoglycemia (21.5%), and Hypothermia. Nearly half (40.4%) of mothers of newborns experience index pregnancy complications Premature Rupture of the membrane (AOR=5.79, 95% CI: 2.08, 16.1), birth weight less than 2500gm (AOR= 3.96, 95% CI: 1.56. 10.06), hypothermia (AOR=2.54, 95% CI: 1.1, 6.02) index pregnancy complications (AOR=4.79, 95% CI: 1.92, 11.91), and induced labor (AOR=4.45, 95% CI: 1.53, 12.94) were significantly associated with neonatal mortality. Conclusion: The prevalence of neonatal mortality was high as compared to the national target. Premature Rupture of the membrane, birth weight less than 2500gm, hypothermia, index pregnancy complications, and induced labor were significantly associated with neonatal mortality. The majority of neonatal deaths are due to complications arising from pregnancy, labor and delivery, and lack of quality of care at the neonatal intensive care unit. Cultivating and increasing the utilization of antenatal care services, quality of care at delivery, and the Neonatal intensive care unit could avert those deaths.